Build an Entrepreneurial Spirit in Society - Delfi Gusnia Delza; Hendri Perwira; Istiva Ahyani; Yulida Hapni Siregar; Rian Vebrianto (Anotero Lembaga Scientific Pekanbaru, 2021)
Entrepreneurship is a creative and innovative ability, keen to see opportunities and always open to any positive input and changes that can bring the business to continue to grow. Businesses should have value and be useful where this can be done through the application of the concept of social entrepreneurship. Various groups began to discuss the concept of social entrepreneurship as an innovative solution in solving social problems. For this reason, service is carried out by KKN children to those who involve villagers. By using an evaluation instrument, it is known that entrepreneurship has a very large role in the development of economic growth. The role of entrepreneurship has been tested by the economic crisis that hit the Indonesian nation. Entrepreneurship based on the people's economy was able to survive in difficult situations. The purpose of social entrepreneurship is the realization of social change for the better or positive and solving social problems for the benefit of society.